2006
DOI: 10.1523/jneurosci.2789-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation of Frontal Oculomotor Regions during Smooth Pursuit

Abstract: Both the frontal eye fields (FEFs) and supplementary eye fields (SEFs) are known to be involved in smooth pursuit eye movements. It has been shown recently that stimulation of the smooth-pursuit area of the FEF [frontal pursuit area (FPA)] in monkey increases the pursuit response to unexpected changes in target motion during pursuit. In the current study, we applied transcranial magnetic stimulation (TMS) to the FPA and SEF in humans during sinusoidal pursuit to assess its effects on the pursuit response to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 64 publications
6
30
0
Order By: Relevance
“…The deficits to pursuit metrics and predictive pursuit are observed for pursuit in all directions but are most strongly expressed for pursuit ipsiversive to the lesion. Similar results have recently been reproduced in humans: transcranial magnetic stimulation of the area during ongoing pursuit reduces eye velocity (Gagnon et al 2006).…”
supporting
confidence: 81%
“…The deficits to pursuit metrics and predictive pursuit are observed for pursuit in all directions but are most strongly expressed for pursuit ipsiversive to the lesion. Similar results have recently been reproduced in humans: transcranial magnetic stimulation of the area during ongoing pursuit reduces eye velocity (Gagnon et al 2006).…”
supporting
confidence: 81%
“…TMS effects on eye movements are not uncommon, but are usually associated with stimulating other brain areas than we did, like the frontal eye fields, and only if eye movement preparation or execution falls within a relatively narrow time window (up to 150 ms) around the TMS pulse (Gagnon et al, 2006;Drew and Donkelaar, 2007;Walker et al, 2009). In our case, visual stimulation did not start until several hundred milliseconds after TMS was applied, and then lasted for another second (see below).…”
Section: Methodsmentioning
confidence: 79%
“…In support of this view, several imaging studies have shown reduced FEF activation in schizophrenia patients or their relatives during SPEM (23)(24)(25). In addition, transcranial magnetic stimulation of FEFs at the time of change in pursuit direction results in acceleration of the eye in the expected target direction (26), suggesting that poor predictive acceleration may be subjected to behavioral improvement using interventions to enhance FEF function. Zaksas and Pasternak (27) illustrated a close interaction between FEF and MT in maintaining oculomotor working memory, which may provide a new framework to unify the findings of abnormal motion perception (4;6) and abnormal predictive pursuit in schizophrenia.…”
Section: Discussionmentioning
confidence: 91%